2020
DOI: 10.1177/0022034520903036
|View full text |Cite
|
Sign up to set email alerts
|

Desensitizing Toothpastes for Dentin Hypersensitivity: A Network Meta-analysis

Abstract: The goal of this systematic review and network meta-analysis was to compare the relative effects of toothpaste formulations for dentin hypersensitivity (DH), tested in randomized controlled trials (RCTs). We searched 7 databases to February 2019. Paired reviewers independently screened studies, extracted data, and performed risk of bias assessment. The outcome of interest was painful response measured through tactile, cold, and air stimuli. We conducted a random-effects Bayesian network meta-analysis using sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 36 publications
0
63
0
4
Order By: Relevance
“…Participants analyzed per group were more than thirty fulfilling the requirement of Holland's guidelines for conducting clinical trials for the management of DH [ 42 ]. Published literature [ 16 , 31 , 43 ] has determined that all previous trials on treating DH were conducted on smaller samples, which might have prevented the results from being extrapolated on the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants analyzed per group were more than thirty fulfilling the requirement of Holland's guidelines for conducting clinical trials for the management of DH [ 42 ]. Published literature [ 16 , 31 , 43 ] has determined that all previous trials on treating DH were conducted on smaller samples, which might have prevented the results from being extrapolated on the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FCPS as a new bioactive material revealed promising potency of sustainable management of DH in a previously conducted trial by Ashwini et al in 2018 [ 17 ]. A head-to-head comparative evaluation of these most effective bioactive agents, such as arginine and BAG-based desensitisers, was suggested by Martins et al [ 18 ] in a meta-analysis in 2020. Hence, the effectiveness of clinically available formulations of FCPS in OTC dentifrices needs further exploration for the permanent management of DH.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SnF2-based formulations seem to be more effective than regular-fluoride toothpastes to manage DH due to tactile and air stimuli with high-to-moderate certainty. [ 31 ] Another systematic review of 74 articles suggested marked long-term reduction in DH with agents such as potassium nitrate, arginine, glutaraldehyde with hydroxyethyl methacrylate (HEMA), hydroxyapatite, adhesive systems, glass ionomer cements, and LASER, whereas short-term relief (1 week) was seen by the use of glutaraldehyde with HEMA, glass ionomer cements, and laser, and intermediate DH reduction (up to 1 month) was seen in stannous fluoride, glutaraldehyde with HEMA, hydroxyapatite, glass ionomer cements, and laser groups. Moreover, in-office treatments were more efficacious for immediate DH reduction and at-home treatments are recommended for long-time effects.…”
Section: Discussionmentioning
confidence: 99%
“…Each outcome was tabulated in a Summary of Finding (SoF) Table using GRADEpro. For the magnitude of the effect, we used the Cohen’s effect sizes for SMD: from -0.2 to 0.2 representing a trivial or no effect; -0.5 to -0.2 or 0.2 to 0.5 representing a small effect; -0.8 to -0.5 or 0.5 to 0.8 representing a moderate effect; and < -0.8 or > 0.8 representing a large effect ( 10 ). The interpretation of the results was based on an integrated approach of the magnitude of the effect based on Cohen’s effect size and the certainty of the evidence ( 11 ).…”
Section: Methodsmentioning
confidence: 99%